Dayak Tunjung Cosmology and the Theology of Communio Sanctorum An Exploration of Contextual Theology in Synthetic Model of Stephen B. Bevans - Yohanes Damianus (Asosiasi Ahli Filsafat Keilahian Indonesia, 2020)
The revelation of God through the history is being permeated in human beings’ culture. Eventually, its proclamation too brought in itself the culture elements. Since, the culture itself is holy, because it is exactly part of the revelation, and one culture can be in dialogue with other (s) one because God has taken the culture as a context for His own revelation. In missiology, theological reflection tries to further offer and define what the church has been doing since its presence, a practice of a contextual theological reflection. In this space of thought, the church doctrine on communio sanctorum will be in dialogue with a Dayak Tunjung cosmology, an effort to make a synthesis between theology and culture so that the two communities can live and grow together in their respective traditions. The synthetic model of contextual theology offered by Stephen B. Bevans will be used as a framework. The reflection will go to make a synthetic model of theology of Dayak Tunjung cosmology and communio sanctorum in its three categories, mainly cosmological, ritual, and communal life. God, through his Holy Spirit, continuously renews the human beings together with their whole culture aspects.